2012
DOI: 10.1021/jp308161x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Solvent-Induced Coil to Helix Conformational Change on the Two-Photon Absorption Spectrum of Poly(3,6-phenanthrene)

Abstract: This paper investigates the effect of solvent-induced conformational changes of poly(3,6-phenanthrene) on their two-photon absorption (2PA). Such effect was studied employing the wavelength-tunable femtosecond Z-scan technique and modeled using the sum-over-essential states approach. We observed a strong reduction of the 2PA cross-section when the sample was prepared in hexane (poor solvent) in comparison to chloroform (good solvent), which is related to the conformation adopted by the polymer in each case. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
1
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 43 publications
0
16
1
2
Order By: Relevance
“…In that study, the authors compared the 2PA cross‐section obtained for thiophene/phenylene‐based polymer containing about 15 consecutive units with a thiophene/phenylene‐based oligomer, where they observed only an increment of about 2.5 times on the 2PA cross‐section for the polymer when compared with the oligomer. In another work, Vivas et al observed a reduction of about 50% on the 2PA cross‐section of poly(3,6‐phenanthrene) when the polymer changed its conformation from coil to helix. The authors explained that the difference was directly related to the decrease in the molar absorptivity, corroborating the nonlinear optical results obtained by Vanormelingen et al, and also the results presented here.…”
Section: Resultsmentioning
confidence: 95%
“…In that study, the authors compared the 2PA cross‐section obtained for thiophene/phenylene‐based polymer containing about 15 consecutive units with a thiophene/phenylene‐based oligomer, where they observed only an increment of about 2.5 times on the 2PA cross‐section for the polymer when compared with the oligomer. In another work, Vivas et al observed a reduction of about 50% on the 2PA cross‐section of poly(3,6‐phenanthrene) when the polymer changed its conformation from coil to helix. The authors explained that the difference was directly related to the decrease in the molar absorptivity, corroborating the nonlinear optical results obtained by Vanormelingen et al, and also the results presented here.…”
Section: Resultsmentioning
confidence: 95%
“…[1,[3][4][5][6][7][8][9][10][11][12][13][14] In 1878, Kundt proposed a rule that related the shift of the UV/Vis absorption-band maximum towards longer wavelengths to the increasing value of the index of refraction. [1,[15][16][17][18] Furthermore, this definition becomes even more broad, covering inter alia solvent effects on fluorescence, [19] Raman and hyper-Raman, [20] as well as twophoton absorption (2PA) [21][22][23][24][25][26][27][28][29][30][31][32][33][34] spectra. [1,[15][16][17][18] Furthermore, this definition becomes even more broad, covering inter alia solvent effects on fluorescence, [19] Raman and hyper-Raman, [20] as well as twophoton absorption (2PA) [21][22][23][24][25][26]…”
Section: Introductionmentioning
confidence: 99%
“…[17,52,53] More recently, RD has gained interest as a material used for model studies of controlled drug delivery [54,55] and as a promising agent for comparing the electrophilicity of various neutral Lewis acidic species. The available data are based on two measurement techniques, that is, Z-scan and two-photon-induced fluorescence (TPIF), [21][22][23][24][25][26][27][28][29][30][31][32][33][34] supported by the results of theoretical studies. [56][57][58][59][60] Since it was first synthesized in 1920, RD and its derivatives have been extensively examined both experimentally, [61] to better understand its unusual sensitivity for changes in the environment, [36-38, 40, 41, 44, 46, 50-60, 62-83] and theoretically.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations